Mechanisms of Thymoquinone Hepatorenal Protection in Methotrexate-Induced Toxicity in Rats - El-Sheikh, Azza A. K. (Mediators Inflamm, 2015)
To investigate mechanisms by which thymoquinone (TQ) can prevent methotrexate- (MTX-) induced hepatorenal toxicity, TQ (10 mg/kg) was administered orally for 10 days. In independent rat groups, MTX hepatorenal toxicity was induced via 20 mg/kg i.p. at the end of day 3 of experiment, with or without TQ. MTX caused deterioration in kidney and liver function, namely, blood urea nitrogen, creatinine, alanine aminotransferase, and aspartate aminotransferase. MTX also caused distortion in renal and hepatic histology, with significant oxidative stress, manifested by decrease in reduced glutathione and catalase, as well as increase in malondialdehyde levels. In addition, MTX caused nitrosative stress manifested by increased nitric oxide, with upregulation of inducible nitric oxide synthase. Furthermore, MTX caused hepatorenal inflammatory effects as shown by increased tumor necrosis factor-α, besides upregulation of necrosis factor-κB and cyclooxygenase-2 expressions. MTX also caused apoptotic effect, as it upregulated caspase 3 in liver and kidney. Using TQ concurrently with MTX restored kidney and liver functions, as well as their normal histology. TQ also reversed oxidative and nitrosative stress, as well as inflammatory and apoptotic signs caused by MTX alone. Thus, TQ may be beneficial adjuvant that confers hepatorenal protection to MTX toxicity via antioxidant, antinitrosative, anti-inflammatory, and antiapoptotic mechanisms.